Same but different? : Measurement invariance of the PIAAC motivation-to-learn scale across key socio-demographic groups - Gorges, Julia [Verfasser]; Koch, Tobias [Verfasser]; Maehler, Débora B. [Verfasser]; Offerhaus, Judith [Verfasser] (My University, 2017)
"Data from the Programme for the International Assessment of Adult Competencies (PIAAC) revealed that countries systematically differ in their respondents’ literacy, numeracy, and problem solving in technology-rich environments skills; skill levels also vary by gender, age, level of education or migration background. Similarly, systematic differences have been documented with respect to adults’ participation in education, which can be considered as a means to develop and maintain skills. From a psychological perspective, motivation to learn is considered a key factor associated with both skill development and participation in (further) education. In order to account for motivation when analyzing PIAAC data, four items from the PIAAC background questionnaire were recently compiled into a motivation-to-learn scale. This scale has been found to be invariant (i.e., showing full weak and partial strong measurement invariance) across 21 countries." (Author's abstract ; BIBB-Doku)
Keywords: S 1.5 Weiterbildung; L 2 Lehr-Lerngestaltung; G 1.3.2 Bildungsverhalten und -verläufe; Weiterbildung; Lernmotivation; Weiterbildungsbereitschaft; Grundbildung; PIAAC